Meningkatkan Kemampuan Berbahasa Indonesia Dengan Menerapkan Model Pembelajaran Think Pair Share - Halijah Halijah (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this study is to improve the ability of Indonesian language by applying the model of think pair share learning. Subjects in this study were the students of class VI SD Negeri 010047 Sei Alim Ulu district Air Batu academic year 2015/2016. The results obtained that the results of the learning process after research improve the ability of Indonesian language by applying the model of learning Think Pair Share on the first cycle reached an average score of 76.5 after motivated conducted research through the cycle II reflection and recommendation average value reached 82.5. Completeness of learning outcomes in the first cycle reached 74.5% after cycle I and cycle II, reflection and learning mastery recommendations in cycle II reached 85.17%. It can be concluded that applying the think pair share learning model can improve Indonesian language ability of grade VI students of SD Negeri 010047 Sei Alim Ulu district Air Batu academic year 2015/2016. Keywords: think pair share, ability to speak Indonesian Abstrak: Tujuan penelitian ini adalah untuk meningkatkan kemampuan berbahasa Indonesia dengen menerapkan model pembelajaran think pair share. Subjek dalam penelitian ini adalah siswa kelas VI SD Negeri 010047 Sei Alim Ulu kec. Air Batu TP. 2015/2016. Hasil penelitian diperoleh bahwa hasil proses belajar setelah penelitian meningkatkan kemam-puan berbahasa Indonesia dengan menerapkan model pembelajaran Think Pair Share pada siklus I mencapai nilai rata-rata 76,5 setelah termotivasi dilakukan penelitian melalui siklus II refleksi dan rekomendasi nilai rata-rata mencapai 82,5. Ketuntasan hasil belajar pada siklus I mencapai 74,5% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan belajar pada siklus II mencapai 85,17%. Dapat disimpulkan bahwa menerapkan model pembelajaran think pair share dapat meningkatkan kemampuan berbahasa Indonesia siswa kelas VI SD Negeri 010047 Sei Alim Ulu kec. Air Batu TP. 2015/2016. Kata kunci: think pair share, kemampuan berbahasa Indonesia